Analisis Konsumsi Energi Protokol Routing Fisheye State Routing (FSR) Pada Mobile Ad Hoc Network (MANET) - Wildan Aulia Rachman; Primantara Hari Trisnawan; Mochammad Ali Fauzi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Mobile Ad Hoc Network (MANET) is a type of ad hoc network that has a dynamic and fast-changing topology in which nodes on MANET are dynamically connected in an orderly manner. In this study Fisheye State Routing (FSR), a routing protocol uses a link state algorithm optimization using the fisheye approach. From the use of these techniques, each node will be grouped according to the distance or hop. In this case the use of energy becomes a matter that needs to be considered in the consumption of energy used in the simulation using NS-2.35. By using energy models, the simulations can produce presentations of energy consumption at nodes with different mobility. the total consumption scenario with the number of nodes 20,30 and 50 in each mobility shows that static mobility has the largest total energy consumption in 2 node scenarios namely 20 and 30 nodes namely 19997,969 and 29995,565 joules but static mobility has less in total energy consumption compared to the other 2 mobility with the use of 50 nodes, which is 499973,065 Joules. In the scenario the average energy consumption has the same results as the total energy consumption scenario. Increasing and decreasing energy consumption in mobility used by different nodes can be influenced by changes in the number of nodes and changes in mobility of each node.